2015
DOI: 10.1016/j.jphs.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the 5-HT1A autoreceptor in the enhancement of fluvoxamine-induced increases in prefrontal dopamine release by adrenalectomy/castration in mice

Abstract: We have found that fluvoxamine-induced increases in prefrontal dopamine release are enhanced by adrenalectomy/castration and 5-HT1A receptors are involved in the enhancement. This study examined which 5-HT1A autoreceptors or postsynaptic receptor play a key role in the enhancement in mice. Adrenalectomy/castration-induced enhancement of fluvoxamine-induced increase in the dopamine release was not blocked by local perfusion with the 5-HT1A receptor antagonist WAY100635 (10 μM), while it was blocked by systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…FM increases serotoninergic neurotransmission via potent and selective inhibition of serotonin (5‐HT) reuptake into presynaptic neurons (Muck‐seler et al, 2012). Among 5‐HT system receptors, the 5‐HT 1A receptors have been shown to be involved in the enhancement of FM‐induced increases in prefrontal DA release and play a key role in the mechanism of action of the drug (Hasebe et al, 2015). The serotonergic system can regulate normal motor functions through stimulation of 5‐HT 1A receptors within the basal ganglia which can result in DA release (Nayebi et al, 2010; Mahmoudi et al, 2011, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…FM increases serotoninergic neurotransmission via potent and selective inhibition of serotonin (5‐HT) reuptake into presynaptic neurons (Muck‐seler et al, 2012). Among 5‐HT system receptors, the 5‐HT 1A receptors have been shown to be involved in the enhancement of FM‐induced increases in prefrontal DA release and play a key role in the mechanism of action of the drug (Hasebe et al, 2015). The serotonergic system can regulate normal motor functions through stimulation of 5‐HT 1A receptors within the basal ganglia which can result in DA release (Nayebi et al, 2010; Mahmoudi et al, 2011, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Picrotoxin was used at doses of 1 mg·kg −1 or less, a subconvulsive dose, to inhibit GABA A receptors (Girish et al, ; Ago et al, ). The doses of the other drugs were those used in previous studies (Koda et al, ; Ago et al, , ,b, ; Hiramatsu et al, ; Hasebe et al, ,b). In the present study, picrotoxin at 1 mg·kg −1 decreased locomotor activity 30–60 min after the injection, but did not affect the locomotor activity on the behavioural assay (100 min after the injection).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously observed that fluvoxamine increases extracellular levels of 5‐HT and dopamine in the prefrontal cortex of normal rodents (Ago et al, ) and that fluvoxamine‐induced prefrontal dopamine release is enhanced by adrenalectomy+castration through a σ 1 receptor‐mediated mechanism (Ago et al, ). Our subsequent studies have shown that the effect of fluvoxamine on prefrontal dopamine release is mediated by an interaction between the presynaptic 5‐HT 1A autoreceptor and the σ 1 receptor in the prefrontal cortex (Hiramatsu et al, ; Hasebe et al, ) and that the GABA A receptor is involved in the adrenalectomy+castration‐induced enhancement of the fluvoxamine‐induced increase in prefrontal dopamine levels (Ago et al, ). These findings provide a novel regulation mechanism for prefrontal dopamine release that is associated with the interactions among the σ 1 , 5‐HT 1A and GABA A receptors.…”
Section: Introductionmentioning
confidence: 99%